Complete plastome sequence of Nepenthes mirabilis (Nepenthaceae): a “vulnerable” herb in China - Zhi-Xin Zhu; Jian-Hua Wang; Chao-Rui Chen; Kun-Kun Zhao; Hua-Feng Wang (Mitochondrial DNA. Part B. Resources, 2018)
Nepenthes mirabilis (Nepenthaceae) is an erect or climbing (0.5–2 m tall) herb distributed in Africa (Madagascar), south and southeast Asia, North Australia and Pacific Islands (Caroline Islands). There is only one species in China. It grows in wet and sandy soils places throughout forests, grasslands, swamps, mountains, roadsides, wastelands having altitudes that sea level to 400 m. It has been ranked as a VU (Vulnerable) species in China. Here we report and characterize the complete plastid genome sequence of N. mirabilis in an effort to provide genomic resources useful for its conservation. The complete plastome is 155,755 bp in length and contains the typical structure and gene content of angiosperm plastomes, including two Inverted Repeat (IR) regions of 26,415 bp, a Large Single-Copy (LSC) region of 84,997 bp and a Small Single-Copy (SSC) region of 17,928 bp. The plastome contains 113 genes, consisting of 77 unique protein-coding genes, three pseudogenes, 29 unique tRNA genes, and four unique rRNA genes. The overall A/T content in the plastome of N. mirabilis is 62.8%. Phylogenetic analyses were performed using the entire plastome, including spacers, introns, etc., and we determined that N. mirabilis 32 and Dionaea muscipula were closely related. The complete plastome sequence of N. 33 mirabilis will provide a useful resource for the conservation genetics of this species as 34 well as for the phylogenetic studies in Caryophyllales.